Managing the High Incidence of Testicular Pain and Pathology in Prisoners with Telemedicine. Issue 5 (September 2018) - Sherwood, Brenton G.; Nepple, Kenneth G.; Erickson, Bradley A.
Abstract : Introduction: : Medical transportation of prisoners involves inherent risks. Telemedicine may allow prisoners to receive appropriate evaluation, testing and treatment with minimal need for transportation. Our medical center manages the urological complaints of all prisoners in our state and uses telemedicine to evaluate patients before transportation. In this study we determined the clinical course of prisoners with testicular pain and pathology, and assessed the safety and potential effectiveness of telemedicine for the evaluation and treatment of these patients. Methods: : We retrospectively reviewed the medical records of all prisoners evaluated by telemedicine from January 2007 to July 2014. Records were examined for urological complaints, diagnoses, initial tests and treatments, outcomes and eventual surgery. The effectiveness of telemedicine was determined by comparing the telemedicine and in‐person visit diagnosis. Results: : There were 376 prisoners with urological complaints, of which 29% were for testicular pain and pathology. Tests were ordered in 78% at the telemedicine encounter (73% ultrasound). Clinic visit followed telemedicine in 49% of cases, of which the telemedicine diagnosis was confirmed in 98%. Elective surgery was performed in 8% and no patients had malignancy. Conclusions: : Testicular pain and pathology represented nearly a third of the urological complaints in this population, all of which were benign with few requiring surgery. It appears that testicular pain and pathology could be mostly managed with telemedicine and testing at local facilities without compromising quality of care, potentially reducing health care expenditure by the prison and health care systems.